Hepatitis C in Patients With Minimal or No Hepatic Fibrosis: The Impact of Treatment and Sustained Virologic Response on Patient-Reported Outcomes. (20th December 2017) - Younossi, Zobair M; Stepanova, Maria; Asselah, Tarik; Foster, Graham; Patel, Keyur; Bräu, Norbert; Swain, Mark; Tran, Tram; Esteban, Rafael; Colombo, Massimo; Pianko, Stephen; Henry, Linda; et al.
Abstract : Treatment of hepatitis C virus with the new direct-acting antivirals in patients with minimal or no hepatic fibrosis provides not only high rates of cure but also significant improvement in patient-reported outcomes (quality of life, fatigue, and work productivity). Abstract: Background: While the necessity of treatment of hepatitis C virus (HCV)–infected patients with advanced liver disease is widely accepted, the benefit of treating patients without significant liver disease is less well established. Our aim was to assess the effect of treating HCV in patients with no or minimal fibrosis (Metavir stage F0–F1) on patient-reported outcomes (PROs). Methods: HCV-infected patients with F0–F1 from 16 clinical trials were included. PROs were collected before, during, and after treatment. Results: A total of 1548 HCV-infected patients with F0–F1 were included (mean age 46 years, 43% male, 81% treatment-naive). Patients were treated with interferon (IFN) + sofosbuvir (SOF) + ribavirin (RBV) (n = 91) or SOF + RBV with or without ledipasvir (n = 479) or IFN- and RBV-free regimens with SOF + ledipasvir or SOF + velpatasvir or SOF + velpatasvir + voxilaprevir (n = 978). By the end of treatment, patients receiving IFN-containing regimens experienced significant decreases in most PRO domains (–4.5 to –28.7 on a 0–100 scale), while subjects treated with IFN-free RBV-containing regimens had a modest impairment (–2.3 to –8.9) (P ≤ .01). In contrast, treatment with regimens without IFN and RBV led to PRO improvements (+1.2 to +10.9). Regardless of the regimen, sustained virologic responses (SVRs) at 12 and 24 weeks were universally associated with PRO improvements (+2.1 to +14.7, P < .0001. Conclusions: HCV-infected subjects with no or minimal fibrosis treated with IFN- and RBV-free regimens experienced on-treatment and post-SVR PRO improvements.